Relationship marketing: The six markets framework - Payne, Adrian (Cranfield School of Management, 1993)
The emergence of relationship marketing in the 1980s has been not so much a discovery, but a rediscovery of an approach which has long formed the cornerstone of many successful businesses. This approach emphasises the development and enhancement of relationships over the customer life cycle rather than new customer acquisition. Despite the increasing recognition of the importance of retention of existing customers, relatively little effort has been directed at developing frameworks and analytical tools to help achieve this. However, recently research activity has focused on the critical activities and issues that need to be managed in order for organisations to achieve increased performance and success in the marketplace through relationship marketing.